2019
DOI: 10.1016/j.scitotenv.2018.10.234
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants removal and bacterial activity enhancement along the flow path of constructed wetland microbial fuel cells

Abstract: Microbial fuel cells implemented in constructed wetlands (CW-MFCs), albeit a relatively new technology still under study, have shown to improve treatment efficiency of urban wastewater. So far the vast majority of CW-MFC systems investigated were designed as lab-scale systems working under rather unrealistic hydraulic conditions using synthetic wastewater. The main objective of this work was to quantify CW-MFCs performance operated under different conditions in a more realistic setup using meso-scale systems w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 63 publications
2
14
1
Order By: Relevance
“…The activity of electrogenic microorganisms has a significant impact on the electrical performance of MFCs. 12,25 According to our work, S. putrefaciens, 26 and these results were consistent with other reports. 12,[27][28][29] Microbial activity affects the electrical performance of MFCs mainly through electron transfer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The activity of electrogenic microorganisms has a significant impact on the electrical performance of MFCs. 12,25 According to our work, S. putrefaciens, 26 and these results were consistent with other reports. 12,[27][28][29] Microbial activity affects the electrical performance of MFCs mainly through electron transfer.…”
Section: Discussionsupporting
confidence: 93%
“…The activity of electrogenic microorganisms has a significant impact on the electrical performance of MFCs 12,25 . According to our work, the addition of SAs reduced the electrical production of MFCs, and production decreased with increased concentrations of SAs; this effect might be associated with the toxic effects of SAs on S. putrefaciens , 26 and these results were consistent with other reports 12,27‐29 …”
Section: Discussionsupporting
confidence: 92%
“…[25][26][27] Other studies have integrated MFC concepts into CW with the purpose of harvesting energy, although the strategy of burying electrodes in the gravel of conventional CW exhibited a minor impact on the wetland performance from the water purification perspective. [28][29][30] In contrast, the METland® concept followed an alternative approach by replacing the classical biofilter material (gravel and sand) with an EC material so bacteria can interchange electrons with the bed. The first METland® was based on horizontal subsurface flow (HSSF), 25 a saturated system in which anaerobic conditions prevailed.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this work, six unplanted meso-scale horizontal subsurface flow (HF) systems were used (a duplicate of systems per treatment: two systems per CW-control, CW-MFC and CW-MEC). The setup of these systems is detailed in a previous study (Hartl et al, 2019). Briefly, the systems consisted of a PVC reservoir of ca.…”
Section: General Designmentioning
confidence: 99%
“…Up to date, there are only a few publications dealing with the use of CW-MFC for OMP removal, and to the authors' knowledge, there are none on the use of CW-MEC systems. Generally, CW-MFC systems have been described to increase the microbial activity (determined by means of fluorescein diacetate (FDA) hydrolysis) in CW-MFC (Hartl et al, 2019), and some studies showed that CW-MFC enhance microbial community richness and diversity as compared to an open-circuit control (Song et al, 2018;F. Xu et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%